Metal ion nano-flaky calcium silicate and its preparation method and application
Through the co -sedimentation method and space -limited domain legal system preparing metal ionic nanocal calcium silicate, the problem of complex and long time of calcium silicate preparation in existing technologies has been solved, and the raw materials are easy to obtain, simple craftsmanship, nano -type structure structure Stable calcium silicate preparation is pretended to show excellent flame retardant effects and strengths in organic silicon sealing.
Patent Information
- Application Number
- CN202411523526.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing calcium silicate preparation process is long, the steps are complex, the raw materials and equipment requirements are high, and the morphology and particle size control is difficult. It is necessary to develop calcium silicate with easy-to-get raw materials, simple processes, and stable nanosheet-like structure.
Adopt a co -sedimentation method and space -limited domain -linked metal ionic nanocal sliced calcium silicate. By adding silicate solutions to the calcium salt saturated solution containing metal salt, it is added to add calcium salt to maintain the excess of calcium salt solution to maintain calcium salt solution. Calcium silicate of nano -type structures is generated.
Calcium silicate preparation with raw materials, simple craftsmanship, and stable nano -chip -shaped structure, and calcium silicate prepared in organic silicon sealing shows excellent flame retardant effects and strengths in organic silicon seals.
Smart Images

Figure CN119038566B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of calcium silicate, and in particular relates to a metal ion nano-flaky calcium silicate and a preparation method and application thereof. Background Art
[0002] Existing methods for preparing calcium silicate include mechanochemical method, hydrothermal synthesis method, sol-gel method and solution method, and their characteristics are as follows:
[0003] The mechanochemical method is to mix siliceous materials, calcium materials and distilled water at room temperature, place them in a ball mill together with steel balls, and perform ball milling to finally obtain calcium silicate slurry. This method has a long reaction time, generally ranging from several hours to several days, and has low requirements for raw materials, but high requirements for grinding equipment; the hydrothermal synthesis method is to mix siliceous materials, calcium materials and water and pour them into a closed reactor. React under a high temperature and high pressure atmosphere, and obtain calcium silicate slurry after the reaction. The reaction time of this method depends on the physical phase of the product, generally ranging from several hours to several days. The composition and morphology of the product can be controlled by adjusting the raw material ratio and the hydrothermal synthesis system, but the energy consumption is high; the sol-gel method is to first react the calcium material with ethanol to obtain an ethanol calcium precursor, and then add the silicon precursor to the solution containing the ethanol calcium precursor, react under certain temperature and stirring speed conditions, and wash the unreacted substances in the reaction product with ethanol and water after the reaction to obtain hydrated calcium silicate. The reaction time of this method depends on the reaction conditions, generally ranging from several minutes to several hours, and the requirements for raw materials and reaction equipment are relatively high; the coprecipitation method is to add a certain proportion of very high-purity alkali silicate and calcium salt to deionized water, adjust the solution pH with calcium hydroxide or sodium hydroxide, and then react under water bath heating conditions to generate hydrated calcium silicate. The reaction of this method is generally completed within a few hours, with lower requirements for equipment, and the variability of the product composition and morphology is also relatively large. The requirements for raw materials are relatively high, and the means of controlling the product particle size are limited.
[0004] Chinese invention patent CN108675312A provides a method for preparing carbide slag-based nanoporous calcium silicate, which comprises the following steps: firstly, ball-milling and calcining carbide slag and a composite metal salt, pouring them into ice water while hot, stirring and mixing, freezing them with liquid nitrogen and thawing them with microwaves for 4 to 8 times, adding urea and urease, stirring and reacting them at a constant temperature, filtering, washing and drying, adding a diluent of ethyl orthosilicate, ultrasonically dispersing them, dripping ammonia water, hydrothermally reacting them, and then filtering, washing and drying them to obtain carbide slag-based nanoporous calcium silicate. This method adopts a mechanochemical method to obtain carbide slag-based nanoporous calcium silicate with a small particle size and uniform distribution; Chinese invention patent CN104030305A provides a method for preparing active calcium silicate, which comprises screening the crushed quicklime, collecting quicklime particles with a particle size of 1-2 cm, mixing them with a silicon source solution for hydrothermal reaction, and vacuum filtering to obtain active calcium silicate. The active calcium silicate prepared by the method has a lower water content, the method is simple and easy, and the raw material cost is low; Chinese invention patent CN114275790A provides a porous hydrated calcium silicate and a preparation method thereof, an adsorbent and an application thereof, wherein fly ash is leached with an alkali agent to obtain a silicate leachate, which is added dropwise to a calcium hydroxide suspension, stirred and heated to obtain a hydrated calcium silicate gel, and azeotropically distilled with an organic alcohol solvent, separated, dried, and roasted to obtain a porous hydrated calcium silicate. The method can obtain a porous hydrated calcium silicate with a larger pore volume and a better pore structure without using a template agent.
[0005] In addition, the coprecipitation method can also be used for preparation. For example, Chinese invention patent CN107673362A provides a method for preparing hydrated calcium silicate, in which a mixture of sodium silicate solution, calcium nitrate solution and water is placed in a plastic container and ultrasonically mixed, the pH value is adjusted with sodium hydroxide solution, nitrogen is sealed, ultrasonically mixed evenly, a constant temperature water bath is used for reaction for a certain period of time, the product is washed and filtered for multiple times, and vacuum dried to obtain a hydrated calcium silicate product. The hydrated calcium silicate prepared by this method has high purity, large single yield, simple preparation process, and good application prospects.
[0006] However, the current process for preparing calcium silicate takes a long time, has complex steps, high requirements for raw materials and equipment, and has simple morphology and particle size. It is necessary to develop a calcium silicate with easily available raw materials, simple process, and stable nano-sheet structure. Summary of the invention
[0007] The present invention provides a metal ion nano-flaky calcium silicate and a preparation method and application thereof. The metal ion nano-flaky calcium silicate is prepared by a coprecipitation method and a spatial confinement method. The raw materials are easily available, the process is simple, and the nano-flaky structure is stable. The metal ion nano-flaky calcium silicate is used together with nano-flaky aluminum oxide to prepare an organic silicon sealant. After high-temperature calcination, the diffusion of harmful gases can be effectively blocked while maintaining good strength.
[0008] The technical solution of the present invention is:
[0009] In a first aspect, a method for preparing metal ion nano-flaky calcium silicate is disclosed, comprising the following steps:
[0010] 1) Weigh calcium salt and metal salt and add them into a reaction flask 1 equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer, place the reaction flask 1 in a constant temperature reaction bath at 20-25° C., add water to dissolve the calcium salt and metal salt, and obtain a calcium salt aqueous solution containing the metal salt, wherein the calcium salt aqueous solution is a saturated solution of the calcium salt;
[0011] 2) Add water to the reaction bottle 2, place it in a constant temperature reaction bath at 20-25°C, add silicate to the reaction bottle 2, stir and dissolve to obtain a silicate aqueous solution;
[0012] 3) Place the silicate aqueous solution in a constant pressure dropping funnel, add it dropwise to the calcium salt aqueous solution containing the metal salt, stir with a stirrer, and use an electric solid adding funnel to add calcium salt solid to the reaction bottle 1 to keep the calcium salt aqueous solution in a supersaturated state until the silicate aqueous solution is added dropwise and precipitate continues to form;
[0013] 4) Centrifuging, washing, drying and grinding the precipitated product to obtain metal ion nano-sheet calcium silicate.
[0014] Preferably, the calcium salt is selected from calcium chloride and calcium nitrate.
[0015] Preferably, the metal salt is selected from one of nickel nitrate, nickel sulfate, copper sulfate, copper nitrate and cobalt nitrate.
[0016] Preferably, the silicate is selected from sodium silicate and potassium silicate.
[0017] Preferably, in step 2), the mass ratio of silicate to water is (3.5-12): (50-150).
[0018] Preferably, in step 3), the dropping speed is 5-15 mL / min, and the supplementary addition speed of the calcium salt solid is 4-22 g / min.
[0019] In a second aspect, disclosed is the metal ion nano-flaky calcium silicate prepared by the preparation method.
[0020] In a third aspect, a silicone sealant is disclosed, and the preparation method is as follows: place the dialkoxy-terminated 107 glue, methyltrimethoxysilane, and silicone oil in a disperser and mix them, add the metal ion nano-flaky calcium silicate and nano-flaky aluminum oxide, disperse and mix them, add a silane coupling agent and dibutyltin disilicate, disperse and mix them, and obtain the silicone sealant.
[0021] Preferably, the added mass ratio of metal ion nano-flaky calcium silicate and nano-flaky aluminum oxide is 1:1.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention drips a silicate solution into a saturated solution of a calcium salt containing a metal salt, and continuously adds calcium salt to maintain the supersaturated state of the calcium salt solution, so that the calcium salt solution participating in the reaction maintains a saturated state, and uses the saturated state of the reaction solution as a confinement region to generate calcium silicate with a nano-sheet structure, and at the same time, metal ions are attached to the calcium silicate. The prepared metal ion nano-sheet calcium silicate has readily available raw materials, a simple process, and the calcium silicate is in the form of nano-sheets with a special interlayer and a stable structure;
[0024] 2. The metal ion nano-flaky calcium silicate prepared by the present invention is added to the silicone sealant as an inorganic filler, which has an excellent flame retardant effect because it cannot burn;
[0025] 3. Under high temperature conditions, the polysiloxane chain segments in the silicone sealant will break and generate free radicals. The free radicals attack other polysiloxane chain segments, causing the degradation of the polysiloxane long chain. The metal ion nano-flaky calcium silicate prepared by the present invention is added to the silicone sealant, so that the silicone sealant contains metal ions. The metal ions can interact with the free radicals to slow down the degradation rate of polysiloxane; when burning, the combustion flame is small. This is because under high temperature conditions, after the polysiloxane chain segments are thermally cracked into small molecules, the volume expands, destroying the colloidal structure, escaping from the colloid, and encountering open flames. When metal ions are present, the thermal cracking rate is slow, the small molecules are few, and the flame is small when burning;
[0026] 4. When the metal ion nano-flaky calcium silicate prepared by the present invention is used as a reinforcing material for silicone sealant, it cooperates with the nano-flaky aluminum oxide, and the negative charge on the surface of the calcium silicate and the positive charge on the surface of the aluminum oxide attract each other to form a dense nano-sheet. After high-temperature calcination, it can effectively block the diffusion of harmful gases while maintaining good strength. When mica powder is used, because the microstructure of the mica powder is not flaky, after the charge adsorption of the nano-flaky aluminum oxide, it still has a large number of pores, which cannot block the passage of harmful gases, and the contact area is small, the colloid strength is poor, and after high-temperature calcination, it is powdered and has no strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the metal ion nano-flaky calcium silicate prepared in Example 1 of the present invention.
[0028] Figure 2 This is a scanning electron microscope image of the metal ion nano-flaky calcium silicate prepared in Example 3 of the present invention.
[0029] Figure 3This is a scanning electron microscope image of the metal ion nano-flaky calcium silicate prepared in Example 5 of the present invention.
[0030] Figure 4 This is a combustion effect diagram of the organosilicon sealant prepared in Example 1 of the present invention.
[0031] Figure 5 This is a combustion effect diagram of the organic silicon sealant prepared by adding mica powder in Comparative Example 1 of the present invention.
[0032] Figure 6 It is a combustion effect diagram (6a) of the organosilicon sealant prepared in Example 1 of the present invention and a combustion effect diagram (6b) of the organosilicon sealant prepared in Comparative Example 2.
[0033] Figure 7 This is a combustion effect diagram of the organosilicon sealant prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0035] Example 1
[0036] This embodiment provides a method for preparing metal ion nano-flaky calcium silicate, comprising the following steps:
[0037] 1) Weigh 149 g of calcium chloride and 2 g of copper sulfate and add them to a four-necked flask equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer. Place the four-necked flask in a constant temperature reaction bath at 20°C, add 200 g of pure water, stir to dissolve the calcium salt and the metal salt, and obtain a saturated aqueous solution of calcium chloride containing copper salt;
[0038] 2) Add 100 g of pure water to a beaker, place it in a constant temperature reaction bath at 20°C, add 7.6 g of sodium silicate to the beaker, stir and dissolve to obtain a sodium silicate aqueous solution;
[0039] 3) Place the sodium silicate aqueous solution in a constant pressure dropping funnel, and add it dropwise to the calcium chloride aqueous solution containing copper salt at a dropping rate of 10 mL / min, stir with a stirrer, and use an electric solid feeding funnel to add calcium chloride solid to the four-necked flask at a solid feeding rate of 8.64 g / min, so that the calcium chloride solution remains in a supersaturated state until the sodium silicate aqueous solution is added dropwise and precipitate continues to form;
[0040] 4) The precipitated product is centrifuged and washed to remove the unreacted soluble salt, dried and ground to obtain metal ion nano-sheet calcium silicate, which is then tested by scanning electron microscopy. Figure 1As shown in the scanning electron microscope image of metal ion nanosheet calcium silicate, the product is slightly circular in shape, with a relatively uniform area, a small diameter of the nanosheets, and they are stacked together in an interlaced manner.
[0041] Preparation of silicone sealant: Use a three-dimensional high-speed disperser to weigh 30g of a viscosity of 20000mm 2 / s alkoxy silicone oil end-capping 107, alkoxy silicone oil end-capping 107 purchased from Ningbo Runhe High-tech Materials Technology Co., Ltd., model RH-FW20K alkoxy silicone oil end-capping 107, 2.5g methyltrimethoxysilane, 10g viscosity 300mm 2 / s of silicone oil, disperse and mix for 20 minutes, add 20g of the product of this example, metal ion nano-flaky calcium silicate and 20g of nano-flaky alumina, the nano-flaky alumina was purchased from alumina nanosheets A100 produced by Nanjing Jicang Nano Technology Co., Ltd., after dispersing and mixing for 20 minutes, add 3g of silane coupling agent KH-550 and 1g of dibutyltin silicate in February, disperse and mix for 10 minutes, and load the prepared silicone sealant into the hose.
[0042] The prepared silicone sealant was squeezed into a 40mm×40mm×2mm mold and cured at 25°C and 50% humidity for 7 days to obtain a test sample 1. The test sample 1 was calcined at high temperature for five minutes using a butane spray gun. Figure 4 After high-temperature calcination, it can effectively block the diffusion of harmful gases while maintaining good strength.
[0043] Example 2
[0044] This embodiment provides a method for preparing metal ion nano-flaky calcium silicate, comprising the following steps:
[0045] 1) Weigh 129g of calcium nitrate and 1g of copper nitrate and add them to a four-necked flask equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer. Place the four-necked flask in a constant temperature reaction bath at 20°C, add 100g of pure water, stir to dissolve the calcium salt and the metal salt, and obtain a saturated aqueous solution of calcium nitrate containing copper salt;
[0046] 2) Add 150 g of pure water to a beaker, place it in a constant temperature reaction bath at 20°C, add 11.4 g of sodium silicate to the beaker, stir and dissolve to obtain a sodium silicate aqueous solution;
[0047] 3) Place the sodium silicate aqueous solution in a constant pressure dropping funnel, and add it dropwise to the calcium nitrate aqueous solution containing copper salt at a dropping rate of 15 mL / min. Stir with a stirrer, and use an electric solid feeding funnel to add calcium nitrate solid to the four-necked flask at a solid feeding rate of 21.38 g / min to maintain the saturation of the calcium nitrate solution until the sodium silicate aqueous solution is added dropwise and precipitate continues to form;
[0048] 4) Centrifuging and washing the precipitated product to remove unreacted soluble salts, drying and grinding the product to obtain metal ion nano-sheet calcium silicate.
[0049] Example 3
[0050] This embodiment provides a method for preparing metal ion nano-flaky calcium silicate, comprising the following steps:
[0051] 1) Weigh 138g of calcium nitrate and 1g of nickel nitrate and add them to a four-necked flask equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer. Place the four-necked flask in a constant temperature reaction bath at 25°C, add 100g of pure water, stir to dissolve the calcium salt and the metal salt, and obtain a saturated aqueous solution of calcium nitrate containing nickel salt;
[0052] 2) Add 150 g of pure water to a beaker, place it in a constant temperature reaction bath at 25°C, add 3.75 g of potassium silicate to the beaker, stir and dissolve to obtain a potassium silicate aqueous solution;
[0053] 3) Place the potassium silicate aqueous solution in a constant pressure dropping funnel, and add it dropwise to the calcium nitrate aqueous solution containing the nickel salt at a dropping rate of 10 mL / min, stir with a stirrer, and use an electric solid feeding funnel to add calcium nitrate solid to the four-necked flask at a solid feeding rate of 14.56 g / min, so that the calcium nitrate solution remains in a supersaturated state until the potassium silicate aqueous solution is added dropwise and precipitate continues to form;
[0054] 4) The precipitated product is centrifuged and washed to remove the unreacted soluble salt, dried and ground to obtain metal ion nano-sheet calcium silicate, which is then tested by scanning electron microscopy. Figure 2 As shown in the scanning electron microscope image of metal ion nano-flaky calcium silicate, the product has a slightly irregular shape, a distinct lamellar structure, and is stacked together in an interlaced manner.
[0055] Example 4
[0056] This embodiment provides a method for preparing metal ion nano-flaky calcium silicate, comprising the following steps:
[0057] 1) Weigh 74.5 g of calcium chloride and 3 g of nickel sulfate and add them to a four-necked flask equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer. Place the four-necked flask in a constant temperature reaction bath at 25°C, add 100 g of pure water, stir to dissolve the calcium salt and the metal salt, and obtain a saturated aqueous solution of calcium chloride containing nickel salt;
[0058] 2) Add 50 g of pure water to a beaker, place it in a constant temperature reaction bath at 25°C, add 5.0 g of sodium silicate to the beaker, stir and dissolve to obtain a sodium silicate aqueous solution;
[0059] 3) Place the sodium silicate aqueous solution in a constant pressure dropping funnel, and add it dropwise to the calcium chloride aqueous solution containing the nickel salt at a dropping rate of 5 mL / min, stir with a stirrer, and use an electric solid feeding funnel to add calcium chloride solid to the four-necked flask at a solid feeding rate of 4.49 g / min, so that the calcium chloride solution remains in a supersaturated state until the sodium silicate aqueous solution is added dropwise and precipitate continues to form;
[0060] 4) Centrifuging and washing the precipitated product to remove unreacted soluble salts, drying and grinding the product to obtain metal ion nano-sheet calcium silicate.
[0061] Example 5
[0062] This embodiment provides a method for preparing metal ion nano-flaky calcium silicate, comprising the following steps:
[0063] 1) Weigh 112.8 g of calcium chloride and 1.5 g of cobalt nitrate and add them to a four-necked flask equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer. Place the four-necked flask in a constant temperature reaction bath at 23°C, add 150 g of pure water, stir to dissolve the calcium salt and the metal salt, and obtain a saturated aqueous solution of calcium chloride containing cobalt salt;
[0064] 2) Add 75g of pure water to a beaker, place it in a constant temperature reaction bath at 23°C, add 6.9g of sodium silicate to the beaker, stir and dissolve to obtain a sodium silicate aqueous solution;
[0065] 3) Place the sodium silicate aqueous solution in a constant pressure dropping funnel, and add it dropwise to the calcium chloride aqueous solution containing the cobalt salt at a dropping rate of 7.5 mL / min. Stir with a stirrer, and use an electric solid feeding funnel to add calcium chloride solid to the four-necked flask at a solid feeding rate of 6.77 g / min to keep the calcium chloride solution in a supersaturated state until the sodium silicate aqueous solution is added dropwise and precipitate continues to form;
[0066] 4) The precipitated product is centrifuged and washed to remove the unreacted soluble salt, dried and ground to obtain metal ion nano-sheet calcium silicate, which is then tested by scanning electron microscopy. Figure 3 As shown, the scanning electron microscope image of metal ion nano-sheet calcium silicate shows that the product has an irregular shape, a sheet-like structure, and is stacked together.
[0067] Comparative Example 1
[0068] In this comparative example, calcium silicate was not prepared but an equal amount of mica powder was used instead.
[0069] Preparation of silicone sealant: Use a three-dimensional high-speed disperser to weigh 30g of a viscosity of 20000 mm 2 / s alkoxy silicone oil end-capping 107, 2.5g methyltrimethoxysilane, 10g viscosity 300mm2 / s of silicone oil, disperse and mix for 20 minutes, add 20g of mica powder and 20g of nano-flaky alumina, disperse and mix for 20 minutes, then add 3g of silane coupling agent KH-550 and 1g of dibutyltin disilicate, disperse and mix for 10 minutes, and load the prepared silicone sealant into the hose.
[0070] The prepared silicone sealant was squeezed into a 40mm×40mm×2mm mold and cured for seven days at 25°C and 50% humidity to obtain test sample 2. After calcining the test sample 2 at high temperature for five minutes using a butane spray gun, Figure 5 After high-temperature calcination, it becomes powdery and has no strength.
[0071] Comparative Example 2
[0072] The preparation method of nano-flaky calcium silicate comprises the following steps:
[0073] 1) Weigh 149 g of calcium chloride and add it to a four-necked flask equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer. Place the four-necked flask in a constant temperature reaction bath at 20°C, add 200 g of pure water, stir to dissolve the calcium salt, and obtain a saturated aqueous solution of calcium chloride;
[0074] 2) Add 100g of pure water to a beaker, place it in a constant temperature reaction bath at 20°C, add 10g of sodium silicate to the beaker, stir and dissolve to obtain a sodium silicate aqueous solution;
[0075] 3) Place the sodium silicate aqueous solution in a constant pressure dropping funnel, and add it dropwise to the calcium chloride aqueous solution at a dropping rate of 10 mL / min. Stir with a stirrer, and use an electric solid feeding funnel to add calcium chloride solid to the four-necked flask at a solid feeding rate of 8.64 g / min. Precipitation continues to form until the sodium silicate aqueous solution is added dropwise;
[0076] 4) Centrifuge and wash the precipitated product to remove unreacted soluble salts, dry and grind it to obtain calcium silicate.
[0077] Preparation of silicone sealant: Use a three-dimensional high-speed disperser to weigh 30g of a viscosity of 20000mm 2 / s alkoxy silicone oil end-capping 107, 2.5g methyltrimethoxysilane, 10g viscosity 300mm 2 / s of silicone oil, disperse and mix for 20 minutes, add 20g of the product of this comparative example calcium silicate and 20g of nano-flaky aluminum oxide, disperse and mix for 20 minutes, then add 3g of silane coupling agent KH-550 and 1g of dibutyltin disilicate, disperse and mix for 10 minutes, and load the prepared silicone sealant into the hose.
[0078] The prepared silicone sealant was squeezed into a 40 mm × 40 mm × 2 mm mold and cured at 25 ° C and 50% humidity for 7 days to obtain test sample 3. The test sample 3 was calcined at high temperature using a butane spray gun. Figure 6 b, without metal ions, the combustion flame is larger. As a comparative example, the high temperature calcination diagram of the organic silicon sealant prepared in Example 1 is shown in FIG. Figure 6 As shown in a, the combustion flame is small. This is because under high temperature conditions, after the polysiloxane chain segments are thermally cracked into small molecules, the volume expands, destroying the colloid structure, escaping from the colloid, and burning when encountering an open flame. When there are metal ions, the thermal cracking rate is slow, there are fewer small molecules, and the flame is small when burning.
[0079] Comparative Example 3
[0080] The difference from Example 1 is that nano-flaky aluminum oxide is not added during the preparation of the silicone sealant. The remaining preparation methods and steps are the same as those of Example 1. Test sample 4 is prepared. After calcining the test sample 4 at high temperature for five minutes using a butane spray gun, Figure 7 As shown, Figure 4 In contrast, the surface after combustion is white. This is because the silicon dioxide generated after the combustion of polysiloxane adheres to the surface. Because it contains copper ions, the inside is purple-red. The difference is that the strength is better after adding alumina nanosheets, and it is not easy to scatter. This is because the surface charges of nano-sheet calcium silicate and alumina nanosheets are opposite, and they adsorb each other, making the colloid stronger and still having excellent strength even after combustion.
[0081] Comparative Example 4
[0082] The difference from Example 1 is that 100 g of calcium chloride is added in step 1), and no additional calcium chloride is added in step 3), and the calcium chloride aqueous solution is in an unsaturated state. The remaining preparation methods and steps are the same as those in Example 1. The reaction cannot generate nano-sheet calcium silicate, and a flocculent precipitate of calcium silicate is obtained, so subsequent experiments cannot be performed.
[0083] The calcium salt in Comparative Example 4 is an unsaturated solution, which loses the confinement domain and cannot generate nano-flaky calcium silicate, but can only be generated in the form of flocculent precipitation.
Claims
1. A method for preparing metal ion nano-flaky calcium silicate, characterized in that: The following steps are involved: 1) Weigh calcium salt and metal salt and add them into a reaction flask 1 equipped with a thermometer, a constant pressure dropping funnel, an electric solid addition funnel and a stirrer, place the reaction flask 1 in a constant temperature reaction bath at 20-25° C., add water to dissolve the calcium salt and metal salt, and obtain a calcium salt aqueous solution containing the metal salt, wherein the calcium salt aqueous solution is a saturated solution of the calcium salt; 2) Add water to the reaction bottle 2, place it in a constant temperature reaction bath at 20-25°C, add silicate to the reaction bottle 2, stir and dissolve to obtain a silicate aqueous solution; 3) Place the silicate aqueous solution in a constant pressure dropping funnel, add it dropwise to the calcium salt aqueous solution containing the metal salt, stir with a stirrer, and use an electric solid adding funnel to add calcium salt solid to the reaction bottle 1 to keep the calcium salt aqueous solution in a supersaturated state until the silicate aqueous solution is added dropwise and precipitate continues to form; 4) Centrifuging, washing, drying and grinding the precipitated product to obtain metal ion nano-sheet calcium silicate.
2. The method for preparing metal ion nano-flaky calcium silicate according to claim 1, characterized in that: The calcium salt is selected from one of calcium chloride and calcium nitrate.
3. The method for preparing metal ion nano-flaky calcium silicate according to claim 1, characterized in that: The metal salt is selected from one of nickel nitrate, nickel sulfate, copper sulfate, copper nitrate and cobalt nitrate.
4. The method for preparing metal ion nano-flaky calcium silicate according to claim 1, characterized in that: The silicate is selected from sodium silicate and potassium silicate.
5. The method for preparing metal ion nano-flaky calcium silicate according to claim 1, characterized in that: In step 2), the mass ratio of silicate to water is (3.5-12): (50-150).
6. The method for preparing metal ion nano-flaky calcium silicate according to claim 1, characterized in that: In step 3), the dropping speed is 5-15 mL / min, and the supplementary addition speed of the calcium salt solid is 4-22 g / min.
7. A metal ion nano-flaky calcium silicate prepared by the preparation method as described in any one of claims 1 to 6.
8. An organic silicon sealant, characterized in that: The preparation method is as follows: bis-alkoxy terminated 107 glue, methyltrimethoxysilane and silicone oil are placed in a disperser for mixing, the metal ion nano-flaky calcium silicate and nano-flaky aluminum oxide described in claim 7 are added, dispersed and mixed, a silane coupling agent and dibutyltin disilicate are added, dispersed and mixed to obtain an organic silicone sealant.
9. The organic silicon sealant according to claim 8, characterized in that: The added mass ratio of metal ion nano-flaky calcium silicate and nano-flaky aluminum oxide is 1:1.
Citation Information
Patent Citations
Method for preparing active calcium silicate
CN104030305A
Method for preparing hydrated calcium silicate
CN107673362A
Preparation method of nano porous calcium silicate based on carbide slag
CN108675312A
Porous hydrated calcium silicate, preparation method thereof, adsorbent and application of adsorbent
CN114275790A
Mesoporous calcium silicate loaded nano zero-valent iron composite material preparation method
CN108031433A